Ultrasound Assisted Esterification of Rubber Seed Oil for Biodiesel Production - Widayat Widayat; Berkah Fajar Tamtomo Kiono (International Journal of Renewable Energy Development, 2012)
Production of biodiesel is currently shifting from the first to the second generation inwhich the raw materials are mostly from non-edible type oils and fats. Biodiesel production iscommonly conducted under batch operation using mechanical agitation to accelerate masstransfers. The main drawback of oil esterification is the high content of free fatty acids (FFA) whichmay reduce the yield of biodiesel and prolong the production time (2-5 hours). Ultrasonificationhas been used in many applications such as component extraction due to its ability to producecavitation under certain frequency. This research is aimed to facilitate ultrasound system forimproving biodiesel production process particularly rubber seed oil. An ultrasound unit was usedunder constant temperature (40oC) and frequency of 40 Hz. The result showed that ultrasound canreduces the processing time and increases the biodiesel yield significantly. A model to describecorrelation of yield and its independent variables is yield (Y) = 43,4894 – 0,6926 X1 + 1,1807 X2 –7,1042 X3 + 2,6451 X1X2 – 1,6557 X1X3 + 5,7586 X2X3 - 10,5145 X1X2X3, where X1 is mesh sizes, X2ratio oil: methanol and X3 type of catalyst.